Efektivitas Salep Ekstrak Etanol Cengkeh (Syzygium aromaticum L) dalam Menghambat Pertumbuhan Bakteri Penyebab Infeksi Kulit - Vara Nabila; Rizki Amelia Nasution; Ulfayani Mayasari (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2024)
This study aims to determine whether clove ethanol extract can be formulated into ointment preparations, evaluate the effectiveness of the ointment in inhibiting bacterial growth causing skin infections, and identify the effective concentration of clove ethanol extract ointment formulation against Streptococcus pyogenes and Pseudomonas aeruginosa. The methods used were disk diffusion and well diffusion with clove ethanol extract concentrations of 10%, 20%, and 30%. Chloramphenicol served as a positive control, and distilled water as a negative control. The ointment formulation was tested at effective doses of 10% and 30% as per Pharmacopeia guidelines. The positive control used bactoderm ointment, and the negative control was an ointment base without clove extract. The results showed that clove ethanol extract could be formulated into an ointment after undergoing phytochemical screening. The clove ethanol extract ointment effectively inhibited bacterial growth causing skin infections. The inhibition zones for Streptococcus pyogenes were 12.16 mm and 14.06 mm, while for Pseudomonas aeruginosa they were 10.16 mm and 9.3 mm. The effective concentrations of clove ethanol extract ointment in inhibiting bacterial growth were 10% and 30%. Keywords: Bacteria, Skin Infection, Clove Ointment